Effectiveness of Structural Education Programme on Prevention of Road Traffic Accidents among Health Science Students - Ramtel, Tara (Journal of Advanced Academic Research, 2024)
Background: Road traffic accidents are primarily caused by ignorance and negligence, and they rank among the top causes of mortality and disability among youngsters. Thus, training and instruction in traffic safety for youngsters should play a significant role in ensuring their safety. Objectives: This study was conducted to assess the effectiveness of a structured teaching program on preventing road traffic accidents in students. Methods: Enumerative sampling was used in a pre-experimental one-group pretest and post-test design. The study included 200 students in Lalitpur, Nepal. Structured knowledge questionnaires were developed. The data was analyzed using descriptive and inferential statistics. Results: The pre-test average knowledge scores were found to be correlated with a number of sociodemographic variables, such as age, religion, educational attainment, employment status, family structure, commute time, mode of transportation, type of accident encountered, being exposed to information on averting traffic accidents, and information source. Among these, the mother's (χ2 = 14.82), father's (χ2 = 9.80), family type (χ2 = 7.50), traveling distance (χ2 = 12.46), mode of transportation (χ2 = 6.89), number of accidents encountered (χ2 = 5.66), being exposed to information about road traffic accidents (χ2 = 25.96), and the source of the information (χ2 = 27.87) were found to be significantly correlated. Conclusion: The samples' understanding of all facets of traffic accidents was insufficient. The results of the study show that the Structural Teaching Program was successful in improving student's understanding of how to prevent traffic accidents.